Pengaruh Program E-Samsat terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Dengan Kepuasan Kualitas Pelayanan Sebagai Variabel Intervening (Studi Kasus Samsat Daerah Istimewa Yogyakarta) - Wardani, Dewi Kusuma (Universitas PGRI Yogyakarta, 2018)
The purpose of this research is to know, the influence of e-samsat program to the satisfaction of service quality, the influence of the satisfaction of service quality to the compliance of motor vehicle taxpayer, the influence of e-samsat program to the compliance of the motor vehicle taxpayers, and to know the effect of e-samsat program on compulsory compliance motor vehicle tax through satisfaction of service quality as intervening variable in Special Region of Yogyakarta. We use primary data. The sample of research is 75 taxpayers but the sample that can be processed only 74.The sampling method used is purposive sampling. Data analysis techniques used path analysis, t test, F test, and R2 test. Based on result of research by using path analysis that, e-samsat program have a significant positive effect to service quality satisfaction, service quality satisfaction has a significant positive effect to vehicle taxpayer compliance, e-samsat program has a significant positive effect on vehicle taxpayer compliance and program e-samsat has a significant positive effect on the compliance of motor vehicle taxpayers through the satisfaction of service quality.Keywords: e-samsat program, service quality satisfaction, and taxpayer compliance